Nutrition of rice as influenced by reclamation techniques for acid sulfate soil in Coxs Bazar (Bangladesh Journal of Scientific and Industrial Research, 2017)
A field experiment was conducted for the reclamation of a Cheringa hot spot of acid sulfate soil manipulated by flash leaching followed by basic slag (BS; BS10 and BS20: basic slag at 10 and 20 t ha-1), aggregate size (A; A20 and A30: aggregate sizes of soil less than 20 and 20-30 mm) treatments under two different techniques (Tech 1: pyrite layer at top, jarosite layer at middle and top soil at the bottom of ridge; Tech 2: top soil at top, pyrite layer at middle and jarosite layer at the bottom of ridge). Nutritional responses to two cultivars of rice with the treatments were evaluated. The initial soil had very low pH (H2O); 3.4, and high EC; 1.6 m S-1, and pyrite content, 76 g kg-1. Magnesium content (5.38 c mol kg-1) of the soil was about 3 fold than that of Ca (1.71 c mol kg-1), and Al content (9.22 c mol kg-1) was at a highly toxic level. The average soil data of all the treatments, except for the control plots after harvesting of rice were increased by 1.5 units for soil pH and 12 to 463% for the contents of N, P, Ca and Mg, while the concentrations of Fe, Al, Na, Cl- and SO4 2- decreased by 27 to 93% compared with the initial soil. The highest N, P, K, Ca, and Mg contents in both the BR 14 and Pizam rice shoots at maturity were obtained by the A20BS30 followed by A20BS20?A30BS30 treatments. The other treatments also resulted in a significant (p?0.05) improved performance on plant nutrition compared with the control. The local Pizam exhibited the best responses under the Tech 2 in order of these nutrient uptakes. Sulfur content in the rice plants on control plots was high (1.8-2.1 g kg-1) but it decreased significantly by the different treatments.Bangladesh J. Sci. Ind. Res. 52(2), 97-106, 2017